Subtitled, streamed, and spoken: Virtual immersion as a pedagogical framework for foreign language learning - Setyanto, Aji; Kewuel, Hipolitus Kristoforus; Prawoto, Sigit; Ismi Prihandari (Englisia Journal, 2025)
This study examines the impact of virtual immersion on foreign language acquisition among Indonesian university students. It specifically explores how learners utilize digital environments—including streaming platforms, social media, and language applications—to develop linguistic proficiency and intercultural competence, and investigates methods for integrating these informal practices into formal curricular structures. Grounded in theories of Second Language Acquisition (SLA), sociocultural theory, and task-based language teaching, the research employed a quantitative-descriptive design. Data were collected via a structured questionnaire administered to 164 multilingual undergraduates studying English, Japanese, French, Chinese, and Korean. Analysis using descriptive statistics and thematic coding revealed that participants actively engage with subtitled media, online communities, and language apps, reporting significant gains in vocabulary and grammatical recognition. However, development in productive skills, particularly oral proficiency, remained limited without scaffolded interaction and feedback. While students exhibited high motivation through self-directed content selection, they identified a critical need for institutional scaffolding, educator training, and technological support. These findings informed the development of a five-component Virtual Immersion Integration Framework, which synergizes authentic digital content, collaborative tasks, intercultural pedagogy, motivational design, and instructional support. This study contributes to the domain of technology-enhanced language learning by providing an evidence-based, scalable model to align informal digital immersion practices with formal higher education curricula in multilingual settings.